El modelo de relaciones colectivas peruano: del intervencionista y restrictivo al promocional - Villavicencio, Alfredo (2012)
The model of peruvian collective relations: from interventionist and restrictive to promotionalThe article begins by considering a system or democratic model of labor relations implies a significant degree of self-gravitating through the presence of collective autonomy as self-regulation agreed in relations between the representatives of workers and employers. That collides with the fact thatin Latin America, with the exception of Uruguay, the model is remarkably restrictive. Although our country since the Constitutionof 1979 explicitly ascribes to the model of Social State of Law – which in the labor field was expressed in the consecration of a democratic model of labor relations, this has not had correlation with the infra-constitutional regulation.Then, the article presents the main characteristics of a democratic model of labor relations which has as main features: i.–The dialectical conception of labor relations and assignment to the conflict of a functional role within the constitutional scheme, ii.– The consecration of collective autonomy as an essential piece of the regulatory system, iii.– The promotional intervention and feeder system from the state as a notion of closure of exceptional transcendence. Finally, the article points out the principalnovelties on the subject contained in the Project of General Labor Law, the same that is in line within the new Latin American context of impulse of the collective autonomy that exists in countries like Brazil, Paraguay, Dominican Republic, Uruguay and also seeks to promote the gradual substitution of decentralized and dysfunctional model for the functioning of the country, establishing a certain preference for the sectorial bargaining.